PENCIPTAAN BUKU POP-UP LEGENDA KETINTANG DENGAN MENGGUNAKAN TEKNIK MOVEABLE SEBAGAI UPAYA KONSERVASI BUDAYA LOKAL SURABAYA - Azizah, Fenny Tri Nur; Bahruddin, Muhammad; Budiardjo, Hardman (Jurnal Art Nouveau, 2016)
Abstract: The purpose of this Creation so that people in Surabaya, especially in the area know of the existence Legend of Ketintang. The creation of this book will use the qualitative method by conducting interviews, observation, and literature to obtain data to supplement and support in the creation of movable pop-up book about the legend of this Ketintang. The data that collected will be analyzed using several techniques, data reduction, data presentation, conclusions or verification, as well as editing a script that will be used in the creation of movable pop-up book is. After analyzing the data, which have been collected are then found a creative concept that is used in the creation of movable pop-up book is that, "Vibrant". "Vibrant" has the sense of the word spirit. The word refers to the spirit of the character Mbah Wijil as the main character, in his determination that wanted to make a haunted forest into the settlements. WithÂ  the technique of movable pop-up kids will be in the spirit of play movable effects pop-ups that are in movable pop-up book about this Legend of Ketintang. So as to make the children to be interested in reading this book will be able to introduce the legend of Ketintang the movable pop-up book as conservation of local culture Surabaya. Keywords: Legend of Ketintang, Movable pop-up, Book, Vibrant